2021
DOI: 10.1016/j.annonc.2021.08.611
|View full text |Cite
|
Sign up to set email alerts
|

328TiP Phase III study of trastuzumab deruxtecan (T-DXd) with or without pertuzumab vs a taxane, trastuzumab and pertuzumab in first-line (1L), human epidermal growth factor receptor 2–positive (HER2+) metastatic breast cancer (mBC): DESTINY-Breast09

Abstract: visceral disease and 89% had non visceral disease. ERI was received in 2 nd , 3rd and 4th line of metastatic treatment for respectively 21%, 44% and 35% pts. Complete response (CR), partial response (PR) and stable disease (SD) were observed respectively for 2.4%, 46.4% and 51.2% of pts.The median duration of response was 25.6 weeks (95 IC 22-27.7) with a median number of infusions of 6. Response was similar irrespective of ERI line number. HD was observed in 70.2% of pts with 3.4% of CR, 50.8% of PR and 45.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…In addition, another head-to-head study (DESTINY-Breast09) was carrying out for the comparison between DS-8201 and trastuzumab. 211 The efficacy and safety of DS-8201 in patients with metastatic NSCLC with HER2 mutations were also assessed in DESTINY-Lung01 study. 212 Among 91 enrolled patients, 55% had a confirmed OR at a median follow-up duration of 13.1 months.…”
Section: Solid Tumorsmentioning
confidence: 99%
“…In addition, another head-to-head study (DESTINY-Breast09) was carrying out for the comparison between DS-8201 and trastuzumab. 211 The efficacy and safety of DS-8201 in patients with metastatic NSCLC with HER2 mutations were also assessed in DESTINY-Lung01 study. 212 Among 91 enrolled patients, 55% had a confirmed OR at a median follow-up duration of 13.1 months.…”
Section: Solid Tumorsmentioning
confidence: 99%
“…The DESTINY--Breast09 study, which enrolled patients with advanced HER2-positive previously untreated breast cancer, is currently ongoing. The results of this study may be very interesting, especially considering safety profile and tolerability, with expected extraordinary effectiveness [20].…”
Section: Trastuzumab Deruxtecanmentioning
confidence: 87%
“…Because BT474 trastuzumab-resistant cancer cells express HER2, we used the anti-HER2 mAb Per in combination with T-DXd as the click approach. Additionally, prior research has shown that T-DXd plus Per is superior to T-DXd alone in treating HER2-expressing tumors (NCT04784715) and others have shown T-DXd efficacy in tumors resistant to trastuzumab ( 43, 46 ). Mice inoculated with trastuzumab-resistant BT474 tumors were treated with T-DXd alone and stratified as responder or non-responders based on their tumor volume ( Fig.…”
Section: Resultsmentioning
confidence: 99%